ANALISIS DAYA TERIMA ANTENA AIRGRID M5HP BERDASARKAN JARAK JANGKAU CLIENT PT. PANGLIMA KAMAYO MEDIA PONTIANAK - PRISMAWAN YURI . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2018)
PT. Panglima Kamayo Media as an internet service provider,  should maintain the quality of its internet network, by looking at one of the benchmarks that is receptivity at the client location influenced by the distance. This research will analyze the influence of the distance range to the power received of  the AirGrid M5HP antenna on each client and to find out about how the distance range affects service performance and provides solutions in order to PT. Panglima Kamayo Media can improve service performance. In this study, it is used a laptop that has installed a browser application as a medium to open AirOS software and to see the received value of the AirGrid M5HP antenna that is undertaken on 10 clients of PT. Panglima Kamayo Media Pontianak. After obtaining the results of the research data, then performed a comparison with the results of calculations and analyzed, which will be drawn conclusions and suggestions regarding power received of antenna AirGrid M5HP client based on the effect within range and also LOS and NLOS conditions on the client of PT. Panglima Kamayo Media Pontianak. There were 2 clients with the results of the measurement of the acceptability of the AirGrid M5HP antenna included in the excellent category (green) based on the reference quality of the power received antenna from the Ubiquiti Network, with a range of ≥ -65 dBm, 4 clients were included in good category (yellow) with range -73 dBm up to -66 dBm, and 4 clients were in enough category (orange) with a range of -80 dBm to -74 dBm. Where the measurement results on 4 clients are included in the category enough (orange)  is a client with NLOS conditions. Clients  both 5 and 6 have low and uneven geographic conditions, in order to a transmitter is needed to be able to connect to the network. Keywords: Power Received Antenna, AirGrid M5HP, Reach Distance, AirOS, Wireless, Line of Sight.